The Effectiveness of Scaffolding Model in Teaching Reading at Senior High Schools - Jufri Jufri (Fakultas Bahasa dan Seni UNP, 2021)
This research is aimed at identifying the students’ ability in reading by using scaffolding teaching model. This is an experimental research that was carried out at senior high school. There were three senior high schools in Padang that became the location of the research, namely SMAN 1, SMAN 7 and SMAN 8 Padang. The population for this research consisted of the students studying at grade X at the three schools respectively. Meanwhile, the sample was taken by using cluster random sampling technique. The whole number of sample was 192 students, namely, 64 students studying at each school. The research instrument used in this research was reading test consisting of 30 items. After carrying the research for about three months the researcher found the result as follows. The findings of the research indicated that the students’ reading achievement taught by scaffolding model was better than those who were taught by conventional model. To prove it, the researcher used t-test formula. The result showed that scaffolding model gave significant effect towards the students reading ability compared to the conventional one.